Induction of Pleomorphy and Calcium Ion Deficiency in Lactobacillus bifidus - Kojima, Masami (1970)
The induction of pleomorphism of Lactobacillus bifidus by NaCl was completely inhibited by CaCl(2). When the organism was cultivated in calcium-free medium, growth of the bifid form was exclusively observed. Supplementation of calcium ion in the medium caused bacilloid growth. Chemical analyses indicated that calcium content of the bifid form organisms was significantly less than that of the bacilloid form; i.e., in the former type, there was an approximately 30% decrease of calcium in the whole cells, and an 82% decrease in the cell wall, as compared with the respective content of the latter. These results indicate a suppressing role of calcium ion in the induction of pleomorphism of L. bifidus. Besides calcium content, sugar and amino acid compositions were shown to be different between the bifid and bacilloid forms. In the cell wall especially, the content of glucose in the bifid form was larger than that in the bacilloid form. Methionine and phenylalanine were present in the bifid form, but not in the bacilloid form. Cell walls of the bifid form organisms lacked a larger molecular weight peptidoglycan (7.5S) which was clearly detected in the bacilloid form. Evidence has been given for the relationships of calcium ion and cell wall components to the pleomorphism in L. bifidus.